KADAR HAEMOGLOBIN PADA BURUH WANITA YANG BEKERJA DI MALAM HARI - Ratih Haribi (JURNAL LITBANG, 2004)
From 30 samples, 19 female labours who have normal and 11 of them have under normal haemoglobine concentration. And than anolized in Chi-Square, so gaining the result reporting there's not significant corelation hetween work hours and haemoglohine concentration. The research samples refers to thefemal.e lobours wha have night work hoursrunge between 5 to l0 hours und more than ten hours.Concerning the extrafooding provided hy Factory, relate with haemoglohine concentration, i.e, l9 female labours who have normal haemoglohine cancentrution, who some of them eat up the extrofooding, 7 of them sometimes eat up antl 3 of them don't eat. Concerning the samples of 30 female labours, I I of them have abnormally haemoglobin concentotion, i.e, 3 female labours don't eut up the extrafooding and 9 don't eut them at all.In conclusion, the average of female lahours who work at night in PT X and who eat up the extrafooding having normal haemoglobine concentration. Meonwhile the female labours who don't eat them have undernormally haemoglobine concentration. The exffafooding provided by PT X is significant against the haemoglobine concentation offemale labours who work at night.Keywords : Haemoglobine, female labours and work at night